Impacts of Saharan dust on downward irradiance and photosynthetically available radiation in the water column - T. Ohde; H. Siegel (Advances in Oceanography and Limnology, 2012)
A semi-empirical approach was used to quantify the modification of the underwater light field in amplitude (magnitude effect) and spectral distribution (spectral effect) by different atmospheric conditions altering the incident light. The approach based on an optical model in connection with radiation measurements in the area off Northwest Africa. Key inputs of the model were parameterized magnitude and spectral effects. Various atmospheric conditions were considered: clear sky, dusty sky without clouds, cloudy sky without dust and skies with different ratios of dust and clouds. Their impacts were investigated concerning the modification of the downward irradiance and photosynthetically available radiation in the water column. The impact on downward irradiance depended on the wavelength, the water depth, the optical water properties, the dust and cloud properties, and the ratio of clouds to dust. The influence of clouds on the amplitude can be much higher than that of dust. Saharan dust reduced the photosynthetically available radiation in the water column. Ocean regions were more influenced than coastal areas. Compensations of the magnitude and spectral effects were observed at special water depths in ocean regions and at atmospheric conditions with definite cloud to dust ratios.